The Mothers, Infants, and Lactation Quality (MILQ) Study: A Multi-Center Collaboration. Issue 10 (20th September 2021) - Allen, Lindsay H; Hampel, Daniela; Shahab-Ferdows, Setareh; Andersson, Maria; Barros, Erica; Doel, Andrew M; Eriksen, Kamilla Gehrt; Christensen, Sophie Hilario; Islam, Munirul; Kac, Gilberto; Keya, Farhana Khanam; Michaelsen, Kim F; et al.
ABSTRACT: Little valid information is available on human milk nutrient concentrations, especially for micronutrients (MNs), and there are no valid reference values (RVs) across lactation. In this multi-center collaborative study, RVs will be established for human milk nutrients across the first 8.5 mo postpartum. Well-nourished, unsupplemented women in Bangladesh, Brazil, Denmark, and The Gambia ( n = 250/site) were recruited during the third trimester of pregnancy. Milk, blood, saliva, urine, and stool samples from mothers and their infants are collected identically at 3 visits (1–3.49, 3.5–5.99, 6.0–8.49 mo postpartum). Milk analyses include macronutrients, selected vitamins, trace elements and minerals, iodine, metabolomics, amino acids, human milk oligosaccharides, and bioactive peptides. We measure milk volume; maternal and infant diets, anthropometry, and morbidity; infant development, maternal genome, and the infant and maternal microbiome. RVs will be constructed based on methods for the WHO Child Growth Standards and the Intergrowth-21st Project. This trial was registered at clinical trials.gov as NCT03254329. Abstract : This article describes the protocol for an international study of human milk composition that will enable the construction of reference values for milk nutrient concentrations during lactation.